AN EMPIRICAL EVIDENCE ON THE IMPACT OF REAL EFFECTIVE EXCHANGE RATE ON TRADE BALANCE - Vivi Elsye Liau; Caroline Geetha (Malaysian Journal of Business and Economics (MJBE), 2020)
This study aimed to examine whether the real effective exchange rate has an impact on trade balance in short run and long run, as well as to investigate if the Marshall-Lerner condition and J-curve phenomenon is satisfied by the variables in Malaysia from 2010 until 2019. Monthly data was used where the dependent variable was trade balance and the independent variable was real effective exchange rate. Several econometric models are applied including the Johansen co-integration to investigate long run relationship and Marshall-Lerner condition estimation, VECM model to investigate short run relationship estimation and impulse response test for J-curve phenomenon estimation. The findings revealed that there was long run relationship between the variables and there was existence of Marshall-Lerner condition. Meanwhile, there was no short run relationship between the variables and J-curve phenomenon was not satisfied in this study. This could be due to devaluation of real effective exchange rate where will help to improve the trade balance in the long run but give a negative effect in the short run which not followed the J-curve pattern. Hence, the Malaysia government should take high concern of exchange rate policy as well as monetary and fiscal policy in order to help stimulate the exports and reduce the inflationary pressure due to devaluation of exchange rate.